Development of Puzzles for Chemical Laboratory Glassware Integrated with Islam as A Learning Medium - Zamhari, Muhammad; Subekti, Zainal Arif; Setiawati, Estriana Murni; Kangkamano, Tawatchai (Journal of Natural Science and Integration, 2022)
The current research seeks to develop and assess the feasibility of puzzles for chemical laboratory glassware integrated with Islam as a learning medium. Conducted through research and development (R&D) method with a 4D model (Define, Design, Develop, and Disseminate), the present project was limited to the Develop stage. The chosen product was a puzzle of chemical laboratory equipment integrated with Islam as a learning medium. The puzzle was applied to 41 students of the chemistry education study program of UIN Sunan Kalijaga who joined laboratory management course. The assessment of the puzzle performance includes ten aspects with 32 indicators. The data obtained was in the form of qualitative and was subsequently tabulated and analyzed using the criteria for the ideal assessment category to determine the quality of the puzzle media. The developed media has a very-good quality according to the assessment among 41 students. The media obtained a score of 142.63 out of a maximum score of 160 and an ideal percentage of 89.15%. The findings disclosed that the developed media is suitable for use as a supporting learning resource for students to understand chemical glassware.Keywords: puzzle learning media; laboratory tools; integration of science and Islam